Learning effects of an experiential groundwater resource game in north-eastern Ghana - Blackmore, Ivy; ElDidi, Hagar; Obuobie, Emmanuel; Akuriba, Margaret; Zhang, Wei; Ringler, Claudia; Meinzen-Dick, Ruth S. (2024)
The growth of dry season farming in Ghana is putting increased pressure on groundwater resources. Using mixed methods this paper examines the learning effect of an experiential groundwater resource game in Ghana’s Upper East Region that simulates real-life resource use and common-pool resource management dilemmas. Results indicate short and medium-term learnings associated with participation in the game. During the game, group interaction and communication improved cooperation and led to more sustainable game behaviors. The positive learning effects from the game persisted 12 months after the intervention. Game participants mentioned sustained lessons learned about the depletable and shared nature of groundwater resources and the importance of communication and collective governance. There were also examples of conscious selection of water conserving crops and the creation community watering schedules to manage water use. Findings highlight the important role experiential learning games can play in fostering real-life behavior change and sustainable natural resource use.